Eksistensi Tradisi Lisan Nandung bagi Masyarakat Melayu Rengat di Kabupaten Indragiri Hulu - Adira, Anisa; Isjoni; Bunari (Jurnal Ilmu Sosial dan Humaniora, 2023)
Nandung oral tradition is one of the oral traditions in the city of Rengat, Indragiri Hulu regency, in the province of Riau. Nandung used to be sung by mothers who wanted to put their children to sleep in the crib. The content of nandung poem is about religious education, parental love, education and nurture, noble character and advice. The aim of this study was to learn about the genesis of the oral Nandung tradition, understand the differences in the oral Nandung tradition in Rengat City, and understand the Nandung oral tradition of Talang Mamak tribe, how the development of Nandung oral tradition in modern times, find out what efforts should be made to maintain Nandung oral tradition and preserve Nandung oral tradition so that it does not experience a shift and knowledge of the process of implementation and implementation of the oral tradition of Nandung itself. The author uses qualitative research methods because in the research the author will interact directly with residents of Rengat City and see first-hand the process of implementing the Nandung Oral tradition. Data collection techniques were performed through observation, interviews and documentation studies. The results of this study explain that at present, the oral tradition of Nandung has undergone a shift that has led to the fact that the oral tradition of Nandung has been forgotten by the people of Rengat City, due to very rapid technological developments. Therefore, efforts by the government, customs and education are needed to preserve the oral Nandunt tradition so that it continues to be recognized by the people of Rengat City.